The Englsih Wits : Literature and Sociability in Early Modern England - Callaghan, Michelle O (Cambridge University Press, 2013)
This book has benefited from its association with many people throughout its various phases. I am indebted to Martin Butler, David Colclough, Margaret Kean, Charlotte McBride, Andrew McRae, David Norbrook, Jennifer Richards, SusanWiseman and Gillian Knight, who took the time to make constructive comments on drafts. Katie Craik read drafts, passed on references and generously shared forthcoming work. Louise Durning, Margaret Healy, Tom Healy, Erica Sheen, Cathy Shrank and Adam Smyth discussed ideas and shared thoughts on sociability. At theHistory of Parliament Trust,Dr Andrew Thrush gave much-needed guidance to early Stuart parliaments, offered useful snippets of information and commented on an early draft of Chapter 4. The two readers at Cambridge University Press gave supportive advice on completing the manuscript. I would also like to thank the librarians at the Bodleian Library, Corpus Christi College library, Oxford and the London Museum as well as the archivists at Hampshire Record Office and the York City Archive for their assistance.